Consensus recommendations for the nutritional management of children with cancer in limited resource settings: a report from the International Initiative for Pediatrics and Nutrition - Viani, Karina; Alves, Jullyana; Damasco-Avila, Erika; Murra, Mariana S.; Schoeman, Judy; Walters, Michelle; Ladas, Elena J. (Frontiers in Nutrition, 2025)
IntroductionMalnutrition (under- and over-nutrition) is a critical challenge in pediatric oncology, particularly in low- and middle-income countries (LMIC), where supportive care resources are scarce. It negatively impacts treatment toxicity, survival rates, and quality of life. Despite the availability of broad guidelines, there is a lack of practical, context-adapted protocols for nutritional assessment and intervention in LMIC. The International Initiative for Pediatrics and Nutrition (IIPAN) developed adapted consensus-based protocols to address this gap.MethodsA multidisciplinary panel of experts in pediatric oncology and nutrition from high-income and LMIC settings collaborated to develop adapted nutrition assessment and intervention manuals. The process involved literature reviews, iterative expert consultations, field testing in LMIC hospitals, and subsequent revisions based on real-world application feedback. Training programs were designed to ensure implementation, including in person and virtual mentorship.ResultsTwo comprehensive manuals and one complementary material were developed: (1) Nutritional Assessment: A Training Manual in Anthropometry, (2) Nutritional Intervention: A Training Manual for Pediatric Oncology, and (3) Appendix for Nutritional Intervention. These resources provide structured detailed guidance on nutrition assessment, interventions, and the management of nutrition-related complications. Their scalability and accessibility are crucial for optimizing nutritional management and improving clinical outcomes in limited resource settings.ConclusionThese evidence-based, expert-designed adapted protocols address critical gaps in nutritional care for children with cancer in LMIC.